ANALISIS DAN EFEKTIFITAS PEMANFAATAN AIR LIMBAH NON DOMESTIK SEBAGAI PEMBANGKIT LISTRIK BERBASIS BIOGAS PLAT, PT. MUSTIKA SEMBULUH POM 1 SAMPIT, KABUPATEN KOTAWARINGIN TIMUR KALIMANTAN TENGAH - Epul Agustian (FT-USNI, 2020)
This study aims to obtain information and determine the analysis and effectiveness of the utilization of non-domestic wastewater as a biogas-based power plant at the PT Mustika Sembuluh POM 1 Sampit plant, Kotawaringin Timur Regency, Central Kalimantan. This research is a quantitative study by collecting data from the field and analyzing data to get conclusions. Based on the resulting quantitative data, both primary data from test results and secondary data from factory performance data, then analyzed to obtain the effectiveness value of related parameters including BOD5, COD, pH, Oil and Fat, Methane (CH4) and Hydrogen Sulfide (H2S) from palm oil liquid waste PT Mustika Sembuluh POM 1 Sampit. The research location is at PT Mustika Pembuluh POM 1 Sampit, Kotawaringin Timur Regency, Central Kalimantan. This research was conducted from November 2019 to May 2020. The results showed that palm oil mills have the potential to become a source of renewable electricity in the form of biogas from liquid waste (POME). PKS performance of PT Mustika Sembuluh POM 1 Sampit, East Kotawaringin Regency, Central Kalimantan is quite good, with the guarantee of raw materials for liquid waste (POME).